The Evaluation of E-Gov Website Service Quality in OKU Regency: E-Govqual and Importance-Performance Analysis Approach - Syla Angra Azhara; Catur Eri Gunawan; Aminullah Imal Alfresi (The Future of Education Journal, 2025)
This research discusses the analysis of the service quality of the OKU Regency website. The aim of this study is to assess the service quality level of the OKU Regency website and to identify which E-Govqual attributes need to be improved and maintained using Importance Performance Analysis (IPA). This study uses E-Govqual and Importance Performance Analysis methods. Data was collected from 270 respondents through a questionnaire. The results show that the service quality score of the OKU Regency website is -0.111. Based on these results, it indicates that the service quality of the OKU Regency website is still low and does not meet user expectations. The analysis of the Importance Performance Analysis quadrant shows that no attributes are in Quadrant A (Main Priority), while Quadrant B (Maintain Performance) contains 10 attributes, Quadrant C (Low Priority) contains 7 attributes, and Quadrant D (Excessive) contains 4 attributes. This research can be used to improve and develop the OKU Regency website by the OKU Regency Communications and Information Office.